A MATLAB primer for technical programming in materials science and engineering - Burstein, Leonid (Woodhead Publishing, 2020)
A MATLAB® Primer for Technical Programming for Materials Science and Engineering draws on examples from the field, providing the latest information on this programming tool that is targeted towards materials science. The book enables non-programmers to master MATLAB® in order to solve problems in materials science, assuming only a modest mathematical background. In addition, the book introduces programming and technical concepts in a logical manner to help students use MATLAB® for subsequent projects. This title offers materials scientists who are non-programming specialists with a coherent and focused introduction to MATLAB®.